Understanding the Buying Behavior of Generation Z Consumers in India: The Parasocial Mediating Role of Influencers on Consumption Tendency - Priya Nair, Sudarshan Seshanna (European Economic Letters (EEL), 2024)
The purpose of this study was to look at how social media exposure affects Generation Z consumers in India's perception of product value, intent to buy, and consumption habits. The study also investigated the effects on these consumer outcomes of influencers' perceived social and physical attractiveness and certain features, like visual appeal, authenticity, perceived usefulness, and social validation. A purposive sample approach was used in conjunction with a qualitative research design to administer structured questionnaires to 750 Generation Z consumers, ages 12 to 22. Regression analysis was used to examine 620 viable replies once partial responses were filtered out to evaluate the proposed hypotheses. The results showed that research participants' perceptions of the worth of items, propensity to buy, and consumption habits were all considerably increased by social media exposure. Furthermore, perceived value, buying intent, Para Social Interaction (PSI), and consumption habits were all highly influenced by influencers' physical and social attractiveness. The study's findings highlight how important social media influencers and platforms are in influencing the attitudes and actions of Generation Z customers. With the use of these data, marketers and brands can create customized marketing plans that appeal to Gen Z's desires for social validation, visual appeal, and authenticity.